A Secure data packet transmission in wireless sensor network using HECC algorithm and Finding malicious packet - Venkateswara Rao, M; Raghava Rao, K (International Journal of Engineering and Technology, 2018)
The most important purpose of implementing to share secure knowledge in encrypted kind in network is to extend the safety of personal networks and its databases and to additionally give remotely infrastructure less secure services globally.Â  In the current system approach ECC elliptic curve cryptography is being used to deal with the security issue in wireless sensor network. Thus the system still get a long packet transfer time, which can be further become a disadvantage while dealing with large data packet. Thus the system further and study require reducing the computation transfer time in between the packet. A proposed hyper elliptic curve mechanism for the cryptography can be used to opt out the best performance over the data packet transfer. In this scenario HECC algorithm is utilized and hence the result outcome shows the efficiency of the algorithm.